Determinantes socio-económicas en la adquisición de viviendas en la ciudad de Machala – Ecuador. - Ordoñez Barberan, Beatriz Adaly (My University, 2020)
This research describes the socioeconomic determinants in the acquisition of homes of the homes of the city of Machala, whose main objective is to measure the probability of own home ownership through a probit model. Throughout history one of the causal factors of concern has been the possession of housing, this problem has arisen mainly in underdeveloped and developing countries, this implies that for families, acquiring a home is a high value investment; globally, housing indicators constitute fundamental sources that show conjecture in social development. The type of research is descriptive, with a quantitative approach, the survey is used as a data collection technique by applying a questionnaire to the heads of the households of the Machala canton, then the probabilistic model is executed which explains that the tenure of housing It is a function of household income, household members between 18 and 65 years of age and employment of the head of the household since these variables have the optimum significance.
Esta investigación describe las determinantes socioeconómicas en la adquisición de viviendas de los hogares de la ciudad de Machala, tiene como objetivo principal medir la probabilidad de tenencia de vivienda propia a través de un modelo probit. A lo largo de la historia uno de los factores causales de preocupación ha sido la posesión de vivienda,, esta problemática se ha presentado principalmente en los países subdesarrollados y en vías de desarrollo, esto implica, que para las familias, adquirir una vivienda es una inversión de gran valor; a nivel global los indicadores de vivienda constituyen fuentes fundamentales que muestran conjetura en el de desarrollo social. El tipo de investigación es descriptivo, con enfoque cuantitativo, se utiliza la encuesta como técnica de recolección de datos mediante la aplicación de cuestionario a los jefes de los hogares del cantón Machala, posteriormente se ejecuta el modelo probabilístico el cual explica que la tenencia de vivienda está en función del ingreso del hogar, miembros de hogar entre 18 y 65 años y empleo del jefe del hogar ya que estas variables tienen la significancia óptima.
Keywords: SOCIO-ECONÓMICO; ECONOMÍA; ADQUISICIÓN; VIVIENDA; MODELO PROBIT